ASHA-community health nurse collaboration for improving maternal and child health outcomes in India: a narrative review - Sneha Dixit; Valarmathi C.; Divya Trivedi; Gurupada K. P.; Ushakiran Thirunavukarasu; Pradeep Kumar; Khumbongmayum Chetanmala Devi; Ghanshyam Singh; S. Tongpangkokla Ozukum; Vidyashri R.; Deepa N. R.; Mohammed Umar (International Journal Of Community Medicine And Public Health, 2026)
India has achieved substantial progress in maternal and child health; however, preventable morbidity, mortality, inequitable access, delayed referral, and discontinuity of care remain important public health challenges. Accredited Social Health Activists and community health nurses occupy complementary positions within the primary healthcare system. Accredited Social Health Activists provide household-level mobilisation, counselling, surveillance, and linkage to health services, whereas community health nurses contribute clinical assessment, risk identification, skilled care, referral coordination, supervision, and continuity across community and facility settings. This narrative review examines how collaboration between these frontline cadres can improve maternal and child health outcomes in India. A structured literature search was undertaken using PubMed, Google Scholar, and relevant government and international health agency sources. Evidence suggests that effective collaboration can strengthen early pregnancy registration, antenatal care utilisation, identification of high-risk pregnancies, birth preparedness, institutional delivery, postnatal follow-up, home-based newborn care, breastfeeding support, immunisation, growth monitoring, and timely referral. However, fragmented communication, role ambiguity, hierarchical relationships, excessive workload, uneven supervision, delayed incentives, inadequate transport, weak referral feedback, and digital fragmentation limit the effectiveness of this partnership. This review proposes the CONNECT-MCH model, an integrated framework based on community identification, ongoing information exchange, nursing assessment and risk stratification, navigation and timely referral, escalation of high-risk cases, closed-loop continuity, and team learning with supportive supervision. Strengthening structured collaboration between Accredited Social Health Activists and community health nurses may transform parallel frontline activities into a coordinated continuum of care and improve equity, responsiveness, continuity, and accountability within India’s maternal and child health system.